B. R. Ambedkar perspectives on social exclusion and inclusive policies - Thorat, Sukhadeo; Kumar, Narender (Oxford Univ. Press, 2008)
Collection of the author's writings on different social issues.
Includes bibliographical references (p. [371]-376) and index
Keywords: Ambedkar, B. R -- (Bhimrao Ramji) -- 1891-1956; Ambedkar, Bhimrao Ramji -- 1891-1956; Geschichte 1919-1956; Politik; People with social disabilities -- Government policy -- India; Affirmative action programs -- India; Reverse discrimination -- India; Quotierung; Indien; Quelle